The Existence of Regional Autonomy Policies In The Islamic Education Institutions of Tangerang District - Misbahuddin Misbahuddin; Syafuri Syafuri; Wasehudin Wasehudin (Dinasti Publisher, 2024)
This research aims to investigate the role of Islamic boarding schools (pondok pesantren) in advancing Islamic education following regional autonomy, particularly within Tangerang District. It also seeks to provide policy recommendations aimed at enhancing the quality of services and the development of pondok pesantren as significant Islamic educational institutions. Employing a combined quantitative and qualitative approach, the study explores the landscape of Islamic educational institutions in Banten post-regional autonomy, with a specific focus on pondok pesantren in Tangerang District, through data collection on school numbers, student enrollment, and a comprehensive literature review. The research findings underscore the positive impact of regional autonomy policies in Tangerang District, notably the Tangerang Religious Program and the Sanitren Program, on the expansion and improvement of Islamic education in the region. These policies have stimulated community interest in religious education at pondok pesantren and have led to enhancements in the educational quality of students, facilitated by incentives for Quranic teachers and advancements in sanitation facilities.